Studying full-shift inhalation exposures to volatile organic compounds (VOCs) among Latino workers in very small-sized beauty salons and auto repair shops - Lothrop, Nathan; Sandoval, Flor; Cortez, Imelda; Wagoner, Rietta; Lopez-Galvez, Nicolas; Parra, Kimberly; Wolf, Ann Marie; Wertheim, Betsy C.; Quijada, Carolina; Lee, Amanda; Griffin, Stephanie; Bell, Melanie; et al. (Frontiers in Public Health, 2023)
Background One in every 200 US jobs is in a beauty salon or auto repair shop, where workers are regularly exposed to volatile organic compounds (VOCs) that may cause a range of short- and long-term health issues. In these shops, Latino workers are overrepresented and lack culturally and linguistically appropriate industrial hygiene resources. This leaves a gap in knowledge on inhalation exposures to VOCs in this hard-to-reach and ubiquitous worker population. Objective Our goal was to recruit hard-to-reach, predominantly Spanish-speaking workers in beauty salons and auto repair shops and monitor total VOC inhalation exposures for over entire work shifts, with minimal impact on workers, clients, and business. Methods We developed and refined measurement and exposure assessment methods for personal and area full-shift VOC inhalation exposures. Results With minimal participant loss, we measured over 500 h of real-time, personal VOC exposures and recorded activities and other exposure factors for 47 participants, while also documenting chemical inventories and quantifying indoor area concentrations of specific VOCs among 10 auto repair shops and 10 beauty salons. Conclusion Lessons learned from our study can assist future studies of inhalation exposures in other hard-to-reach occupational populations.